Ionic liquid driven Refined functionalization of graphene oxide: An insight via combined experiments and theory - Kewat, Heera Lal; Dutta, Debangkana; Ajithkumar, T. G.; Chavda, Dhruvil; Sharma, Rahul Kumar; Tiwari, Mrityunjay K.; Sidiqi, Ubaid; Manna, Moutusi; Nigam, Sandeep; Ghosh, Pushpal (Carbon, 2025)
Functionalizing graphene and its derivative, or doping them with heteroatoms can significantly enhance their optoelectronic, photonic and bio-photonic properties; but controlled and tuneable functionalization of GO is still in their infancy. Herein, a series of functionalized graphene oxide (FGO) are synthesized solvothermally by using task specific ionic liquids (ILs) of varying alkyl chain length; 1-alkyl-3-methylimidazolium tetra fluoroborate, [Cnmim]BF4 (n = 2, 4 etc.). ILs are not only used as a solvent but also as source of fluoride ion for functionalization of GO. A drastic decrease in the oxygen containing functional groups of GO upon fluorination is evidenced by FTIR, Raman, XPS, EDX analysis and electrochemical study. Solid state 19F NMR spectroscopy indicates that, fluorination happens exclusively in edge positions, not on basal planes. Band gap of FGOs decreases along with increasing the chain length of ILs. Further, intense blue emission and high photocatalytic efficiency, using crystal violet as model dye are observed for all the FGOs under visible light. The tailored functionalization by varying alkyl chain length of IL has been rationalized by DFT calculations. It has been realized that owing to the ease of dissociation for [Cnmim]BF4 complexes with n >= 10; greater extent of fluorination/functionalization of GO has been observed. Elimination of a non-covalent interaction on increasing the alkyl chain length has been attributed for lower stability of higher chain length IL which in turn renders ease of dissociation. Easy yet controlled functionalization of GO using tuneable ILs can open a new direction in the environment friendly synthesis and applications.
Keywords: fluorination; Functionalization; graphene oxide; ionic liquids; Luminescence; Photocatalysis